Characteristics of Sirah Nabawiyyah in Sundanese Region: Analysis of the Wawacan Riwayat of Prophet Muhammad - Abdurrohman, Irwan; Ramdani, Acep Dani; Mubarok, Muhamad Raihan Syahrul (Hanifiya: Jurnal Studi Agama-Agama, 2025)
Sirah Nabawiyyah is an important instrument for understanding Islamic teachings comprehensively. Because it documents the practices of practicing the Qur’an directly by the Prophet SAW. For this reason, scholars from the early generations paid more attention to the sirah nabawiyyah, to the point that a lot of literature appeared about it. However, each Sirah nabawiyyah literature has different characteristics according to the situation and conditions at the time it was written. This research will analyze the characteristics of the Sirah nabawiyyah manuscript "Wawacan Riwayat Kangjeng Nabi Muhammad SAW." The method used in this research is analytical descriptive by means of a literature study. The results of this research show that the Sirah nabawiyyah literature in Sundanese Land, the text "Wawacan Riwayat Kangjeng Nabi Muhammad SAW," was written based on the situation and conditions of the Sundanese people at that time who really liked Beluk performances, where texts were read and displayed.